Central Bank Performance under Inflation Targeting - Gosselin, Marc-André (Bank of Canada, 2007)
The inflation targeting (IT) regime is 17 years old. With practice of IT now in more than 21 countries, there is enough evidence gathered to take stock of the IT experience. In this paper, we analyze the inflation record of IT central banks. We extend the work of Albagli and Schmidt-Hebbel (2004) by looking at a broad range of factors that can influence inflation target deviations and by identifying the empirical determinants of successful monetary policy under IT. We find that part of the cross-country and time variation in inflation deviations from targets can be explained by exchange rate movements, fiscal deficits, and differences in financial sector development. With respect to the components of the IT framework, we find that a higher inflation target and a larger inflation control range are associated with more variable inflation (and output) outcomes. Although the literature tends to suggest that greater central bank transparency is desirable, our findings imply that transparency might be associated with less satisfactory inflation performance. Interestingly, central banks using economic models do a better job of stabilizing inflation around the target and output around trend.

Les régimes de cibles d'inflation ont 17 ans. Aujourd'hui, une vingtaine de pays les ont adoptés. On dispose donc de suffisamment de données pour dresser un bilan. L'auteur évalue les résultats obtenus sur le front de l'inflation par les banques centrales qui se sont dotées de cibles. Il étoffe à cet effet le travail d'Albagli et Schmidt-Hebbel (2004) en élargissant le nombre des facteurs susceptibles d'induire des écarts par rapport au taux d'inflation visé et en cernant les déterminants empiriques du succès de la politique monétaire en régime de cibles d'inflation. Il constate qu'une partie des écarts relevés parmi les pays et dans le temps peut être imputée aux mouvements de change, aux déficits des finances publiques et aux différences de développement du secteur financier. En ce qui concerne les caractéristiques proprement dites des régimes, il ressort que le niveau de l'inflation et de la production varie d'autant plus que le taux visé est élevé et que la fourchette de maîtrise de l'inflation est large. À l'encontre des résultats présentés dans la littérature, qui sont favorables à une plus grande transparence de la part des banques centrales, ceux de l'étude donnent à penser que le comportement de l'inflation se détériore en présence d'une transparence accrue. Fait intéressant, les banques centrales qui emploient des modèles économiques réussissent mieux à maintenir l'inflation près de la cible et la production près des valeurs tendancielles.